Safe Scale: A Fire Risk Assessment Mobile - Arumugam, Prem; Reka Ramachandiran, Chandra; Nik Ab Aziz, Nik Sakinah (International Journal of Psychosocial Rehabilitation, 2019)
Fire Risk Assessment is a systematic procedure done to evaluate and determine potential hazards in the case of a fire and the consequences of it. Methods that are done to carry out this procedure can be qualitative, quantitative or a mixture of both. Fire Risk Assessment are done to ensure fire prevention systems in buildings. During Fire Risk Assessments, only a visual inspection is done and through testing is done only if necessary. These assessments are also a legal requirement in most countries which ensure safety of the building’s occupants. Legislations give high priorities to Fire Risk Assessment as they help prevent the risk of fire and minimise the damage cause from a fire by enforcing law to complete Fire Risk Assessment regularly. Currently, the Fire Risk Assessments are done manually by filling up forms, guides and surveys, Guidelines are provided by the respective authorities in each country which is not standardised. Therefore, this research aims to propose a mobile application to conduct and assist the Fire Risk Assessment procedures.